The effects of instructional design based web course on pre-service teachers’ competencies - M. Anas Thohir; Moh. Irma Sukarelawan; Jumadi Jumadi; Warsono Warsono; Alfina Citrasukmawati (Institute of Advanced Engineering and Science, 2021)
Web Pedagogical Content Knowledge (WPACK) is an important competence for pre-service teachers in the educational technology course. However, novice pre-service teachers require the preparation stage to integrate the Web into instruction. The purpose of the study was to develop and to investigate the new instructional model for pre-service teachers in integrating the Web. The Preparation, Isolation, Transformation, Action, Reflection, and Revision (PINTARR) and two other models were implemented in three physics education technology groups with seventy-four participants. The instrument test was constructed to assess the pre-service teachers’ competencies, namely Student analysis, Curriculum organization, Instructional strategy selection, Evaluation, Technological knowledge, and Physics knowledge. The result of MANOVA showed pre-service teachers in PINTARR group outperformed overall the pre-service teachers’ competencies rather than the Multimedia and Web Design Learning group. The results indicated that the Preparation and the Isolation stage were the most important for novice pre-service teachers in improving the competencies.